The outburst radial velocity curve of X-Ray Nova Scorpii 1994 (=GRO J1655--40) - Phillips, S; Shahbaz, T; Podsiadlowski, P (Oxford University Press, 1999)
We present a re-analysis of the outburst radial velocity data for X-ray Nova Scorpii 1994. Using a model based on X-ray heating of the secondary star, we suggest a more realistic treatment of the radial velocity data. Solutions are obtained in the (K2, q) plane which, when combined with the published value for the binary mass ratio and inclination, constrain the mass of the black hole to within the region 4.1